Microsecond charge separation at heterojunctions between transition metal dichalcogenide monolayers and single-walled carbon nanotubes. Issue 10 (19th July 2019) - Sulas-Kern, Dana B.; Zhang, Hanyu; Li, Zhaodong; Blackburn, Jeffrey L.
Abstract : Heterojunctions of transition metal dichalcogenide monolayers and single-walled carbon nanotubes are promising for photocatalysis and photocurrent generation, with microsecond timescale charge separation and sub-picosecond interfacial charge transfer. Abstract : The use of monolayer transition metal dichalcogenides (TMDCs) for optical-to-electrical or optical-to-chemical energy conversion can be limited by the ultrafast excited state relaxation inherent to neat monolayers. Photoinduced charge separation at nanoscale heterojunctions is an important strategy to extend carrier lifetimes, enabling photodetectors, solar cells, and solar fuel production with these ultrathin materials. We demonstrate TMDC/single-walled carbon nanotube (SWCNT) heterojunctions with exceptionally long, microsecond timescale, charge separation following sub-picosecond interfacial charge transfer. These carrier lifetimes are orders of magnitude longer-lived than in other monolayer TMDC heterojunctions. We further present two unique methodologies for estimating charge-transfer quantum yields in MoS2 that can be broadly applied and refined for other TMDC systems. Our results highlight the promise of TMDC/SWCNT heterojunctions for advanced (photo)catalytic and optoelectronic systems and devices.